BUSINESS COMPETITIVENESS IMPROVEMENT ANALYSIS ON DRY FISH PROCESSING INDUSTRY IN BENGKULU CITY - Evanila Silvia; Sigit Mujiharjo; Yuwana Yuwana; Kurnia Herlina Dewi (Jurnal Agroindustri, 2015)
Purpose of this research was to identify environmental factors in terms of strength, weakness, opportunity, and threat influencing dry fish processing industry position, and formulating strategic to improve competitiveness the dry fish processing industry in Bengkulu City.  Method applied was descriptive analysis using SWOT matric, EFE matric, IFE matric.  Research location was in Bengkulu City which was selected on purpose. Respondents were academic (1 person), bureaucrat (1 person), practical person (2 person). Result of the research showed that the internal factor consisted 12 strength strategic factors and 15 weakness strategic factor.  The external strategic factor was composed by 13 opportunity strategic factors and 6 threat strategic factors. Strategic factor being capable to improve competitiveness were 1) product diversityin term of labeland market segment, 2) quality product improvement that capable to specify, and 3) improve sale service.